The hidden challenge: pelvic floor symptoms and their impact on performance and well-being in elite female rugby players - Dakic, J.; Perraton, L.; Lindstrom, J.; Hain, E.; Chuah, S.; Stay, S. (European Journal of Sport Science, 2025)
More than half of female ball-sport athletes experience urinary leakage including 60% of Australian rugby union players. Beyond urinary incontinence (UI), the prevalence and impact of other pelvic floor (PF) symptoms in elite female athletes remains largely unknown. This study investigated PF symptom prevalence and impact on performance in elite female rugby players. A cross-sectional observational study was conducted. Australian elite female rugby players (n = 56) completed a PF questionnaire during annual medical screening. Validated questionnaires established: presence/severity of UI (ICIQ-UI SF), presence and bother of PF symptoms (PFBQ), urinary tract infection, constipation, voiding difficulty (APFQ) and pelvic pain (adapted UDI-6). Purpose-designed questions established symptom impact on performance and well-being. Data were analysed descriptively. Response/questionnaire completion rates were > 95%. Participants were on average: 22.4 years (SD: 5.9); BMI 26.3 kg/m2 (SD: 4.6); mostly nulliparous (94%) and played 6.5 years of rugby (SD: 4.4). More than half (57%) experienced PF symptoms during sport, most commonly UI (41%). Other PF symptoms experienced during sport included: AI (29%), bladder urgency (21%)/frequency (14%) and pelvic pain (12%). One in two symptomatic players reported an impact on performance (53%) including training reductions (34%); activity avoidance (25%) and concentration loss (9%). Players restricted fluid intake to avoid provoking symptoms. A quarter of players reported PF symptoms that impacted their sports performance. This is the first study to establish that, beyond UI, AI, bladder urgency/frequency and pelvic pain are also prevalent in elite rugby players. Elite female rugby players require assessment and management of PF symptoms to maximise performance and well-being.